Developmental progress of CRISPR/Cas9 and its therapeutic applications for HIV‐1 infection. (19th July 2018) - Deng, Qiudi; Chen, Zisheng; Shi, Lei; Lin, Huafeng
Summary: The CRISPR/Cas9 system has been developed as a powerful tool for targeted gene editing. As a result of technical enhancements in recent years, this technology has become the method of choice for efficiently modifying targeted HIV‐1 genome efficiently as part of HIV therapy. CRISPR can be modified to target specific sequences that Cas9 then cuts. In this article, we outline the development of the CRISPR/Cas9 system. We also show how this technology can be used for the prevention and treatment of HIV‐1 infection. Optimistically, this technology promises to make a significant impact on the fight against HIV‐1 in the future.